2015
DOI: 10.3892/ijmm.2015.2242
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 reduces aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells

Abstract: Aldosterone is a steroid hormone secreted from the adrenal cortex, which regulates blood pressure. Higher concentrations of aldosterone can cause several diseases, including hypertension, diabetic nephropathy and chronic kidney disease. Previous reports have demonstrated that aldosterone has a pathogenic role in renal injury via reactive oxygen species (ROS), which involves the regulation of autophagy. However, whether aldosterone can induce autophagy in renal tubular cells remains to be elucidated. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Interestingly, in a report it was shown that Rg1 inhibited angiotensin II-induced podocyte autophagy via the AMPK/mTOR/PI3K pathway [37]. However in another study, Rg1 was demonstrated to reduce aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells [38]. Similarly, Rb1 was reported to have positive [39] and negative [40] effects on neuronal autophagy, respectively, in two different papers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a report it was shown that Rg1 inhibited angiotensin II-induced podocyte autophagy via the AMPK/mTOR/PI3K pathway [37]. However in another study, Rg1 was demonstrated to reduce aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells [38]. Similarly, Rb1 was reported to have positive [39] and negative [40] effects on neuronal autophagy, respectively, in two different papers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that pests rarely feed on the stems and leaves of wild ginseng, which is highly associated with the content of ginsenosides . Recent studies have discovered that the total ginsenosides exhibited significant antifeeding and growth inhibition activities against Mythimna separata (Walker) larvae . Further mechanistic studies revealed that the total ginsenosides reduced the protein content and the activity of digestive enzymes, inhibited the activities of acetylcholinesterase and glutathione s‐transferase, and disturbed the original dynamic balance of protective enzymes (e.g., superoxide dismutase, chloramphenicol acetyltransferase, and peroxidases) .…”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 96%
“…Recent studies have demonstrated that excessive autophagy triggered by the generation of ROS is involved in renal cell injury, particularly podocytes, induced by high levels of aldosterone and angiotensin II . Thus, maintaining the homeostasis of autophagy may be a mechanism of reducing renal injury.…”
Section: Cellular Stress Response Mechanisms Regulated By Ginsenosidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, ginsenoside‐Rg1, the major active ingredient of ginseng, has attracted great attention not only in China, but also in Japan, Korea, and other western countries, due to its extensive pharmacological activities, including neuroprotective and nootropic effects, as well as anticancer, antioxidant, and anti‐inflammatory properties (Zhang et al, ; Mochizuki et al, ; Li et al, ). Interestingly, previous studies have shown that Rg1 can reduce autophagy in cardiomyocytes treated with hypoxia/reoxygenation (Zhang et al, ), and in renal tubular cells exposed to aldosterone (Wang et al, ), suggesting the anti‐autophagy property may be another pharmacological activity of Rg1, which may also inhibit ANG‐II‐induced autophagy in podocyte.…”
Section: Introductionmentioning
confidence: 97%